Theoretical Model of the Fendona® 30 EC Curtain Based on Intervention: Antacedents, Prospects and Recommendations as Dengue Hemorrhagic Fever Control - Meihindra Cahyo Suci Wardoyo; Indasah Indasah (Journal for Quality in Public Health, 2021)
AIM Research developed a theoretical model of the Fendona® 30 EC Curtain based on intervention. The model was developed to enhance understanding of the community's abundance control program. The model analyzes of the variables historical and knowledge of Dengue Hemorrhagic Fever (DHF), the perception of mosquito disorders, the use of mosquito control and medication, the perception of abundance of mosquitoes, the motivation to use curtains, the expected benefits of curtains, the prospects and recommendations of curtains as a mosquito control device. Method Materials: White curtain fabric for window curtain and inter-room bulkhead, black curtain fabric for jar cover, jar filled with plain water, 20cm high, 20cm in diameter, Fendona® 30 EC and clean water Procedures: The curtain is soaked for 24 hours in a liquid of Fendona® 30 EC + water in a ratio of 1: 1; The curtains are dried in a shaded environment for 24 hours, or until the curtains are completely dry. Trials: In-room experimental results show Fendona® 30 EC Curtain effectively prevents mosquitoes from entering the room and kills mosquitoes in the room. Interventions: Curtains installed in the window and as an inter-room divider; The curtain of the jar cover is placed in various corners of the room and under the bed; Each house receives 5 window curtains, 2 curtains screens between rooms and 5 jar cover curtain. Research design: Research uses quasi-experimental design and correlational research surveys. Research data obtained through questionnaires, tests, and check-lists. Research data were analyzed using Regression Path Analysis. Research results Mosquito control programs in the community are difficult to understand. The Fendona® 30 EC curtain, although effective, does not shift the popularity of the mosquito repellent lotion, mosquito spray and mosquito coil. The history of DHF only predicts the perception of mosquito disorders. The perception of a decrease in mosquito abundance can only be predicted from the use of mosquito controls and medicines. Motivation of the use of curtains only predicts the expected benefits of curtains. Recommendations can only be predicted through prospects. Regression paths between variables are separate. Apart from these variables, there is no relationship in the rest of the regression path.